Fungivorous butterflies (Lepidoptera: Nymphalidae): A rare record of feeding behavior - Gilcélia Melo Lourido; Adrya da Silva Figueiredo; Paulo Eduardo Guzzo Coutinho; Raymê dos Santos Carvalho; Kelve Franklimara Sousa Cézar (Revista Chilena de Entomología)
In this work, we report a rare feeding behavior, where adults of two species of frugivorous butterflies were feeding on fungi, Hamadryas februa februa (Hübner) on Auricularia cornea Ehrenb., and Pierella lena brasiliensis (Felder & Felder) on Phallus indusiatus Vent. These events occurred between April and May 2024 in two distinct areas: the first at Campus I of the Instituto Nacional de Pesquisas da Amazônia (INPA) and the second at the Museu da Amazônia (MUSA), both in Manaus, State of Amazonas, Brazil. The rarity of mycophagy events involving Lepidoptera adults, as observed twice here, suggests a potential for the dispersal of fungal spores and underscores the need for more studies to further explore the relationship between these taxonomic groups.